Crimes et châtiments dans le monde de la finance pendant les années Bush - Régine Hollander (Revue LISA)
George W. Bush’s first presidential term was shaken by a series of scandals in the corporate and financial world. Congress and regulatory authorities responded by enacting a wave of reforms. The Sarbanes-Oxley Act, passed in 2002, aimed at increasing financial controls and preventing corporate fraud. Simultaneously, in order to show that crime does not pay and restore investors’ confidence, the Bush Administration set up a task force to crack down on corporate and individual fraud. Firms paid heavy fines. With extended powers granted by the Martin Act, New York’s Attorney General, Eliot Spitzer, relentlessly prosecuted perpetrators. Those found guilty of arrogance, lying or abuse of privileges were sentenced to jail and/or banned from practising their professions. Whistle-blowing was encouraged. Sarbanes-Oxley, however, had pernicious effects on the activity of New York’s financial markets. It discouraged IPOs and incited firms to delist. Some called for deregulation in order to make New York more attractive to publicly-listed companies. But, in September 2008, the mayhem born of the securitization of subprime loans turned into a maelstrom that engulfed the most prestigious Wall Street institutions. Regulators were back in the limelight and risk was nationalized, punishing U.S. taxpayers for a crime for which they denied responsibility. The effect of the financial crisis on Main Street leads to a change in paradigm. Rather than punish a collapsing banking system, the moment has come to save what is left of it to preserve the American way of life.